Monetary Policy and Economic Growth of SAARC Countries - Gajurel, Ram Prasad (Journal of Management, 2023)
The debate on economic policies continues in both the local and global economies. All of the academics are interested in monetary and fiscal policy and how it affects the economy. The study attempts to explore whether there is any evidence that the SAARC countries' economic growth can be influenced by monetary policy. The study applies the Pedroni cointegration approach for panel autoregressive distributed lag (ARDL) with the Pooled Mean Group (PMG) to study the relationship between monetary policy and economic growth of six SAARC nations over the period from 1983 to 2020. The recent study addresses the empirical gap within the context of the southeastern regions of the globe. Overall stylized facts show that monetary policy is causally linked and successful in the long run to accelerate economic growth. Money supply, one of the most crucial variables under study, contradicts the monetarist claim that monetary policy is too effective in the short term. The study also notes that currency devaluation is a serious concern for both short- and long-term growth while inflation is only a short-term one. In the SAARC countries, domestic credit to the private sector is better for short-term economic growth even though it has no long-term benefits. Thus, monetary authorities and the government of the SAARC nations should maintain an adequate level of money supply, adopt an export-led policy to appreciate currency, promote short-run domestic credit to the private sector, and stabilize the short-term price level to accelerate economic growth and development.